LABOR SATISFACTION AND PERFORMANCE AMONG EMPLOYEES OF THE “LLERMAT SÚPER POLLO” COMPANY - Hernandez MedinaPatricia; Bastidas, Isabel; Albarracín, María (UTC Prospectivas: Revista de Ciencias Administrativas y Económicas, 2021)
This research aimed to determine the relationship between satisfaction and work performance among employees of the Llemart Súper Pollo company. In order to address this need, three questionnaires were used to collect data, which were focused on job satisfaction, job performance, and self-evaluation of performance. The results of job satisfaction and performance by location were compared through a contrast of means, an estimation using ordinary least squares to identify the possible relationship between satisfaction and performance, and finally, a factorial analysis to try to summarize all the approaches in dimensions. As a result, it was observed that in general terms, job satisfaction in the company was very good, while job performance and self-evaluation of performance ranged from good to very good, thus coinciding with the two evaluations carried out respectively. It was concluded that there is no significant relationship between job satisfaction and performance among the employees; however, there are differences according to location